2013
DOI: 10.1016/j.biortech.2013.02.095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus load on nutrients removal and N2O emission during low-oxygen simultaneous nitrification and denitrification process

Abstract: Three laboratory scale anaerobic-aerobic (low-oxygen) SBRs (R1, R2 and R3) were conducted at different influent phosphorus concentration to evaluate the impacts of phosphorus load on nutrients removal and nitrous oxide (N₂O) emission during low-oxygen simultaneous nitrification and denitrification (SND) process. The results showed that TP and TN removals were enhanced simultaneously with the increase in phosphorus load. It was mainly caused by the enrichment of polyphosphate accumulating organisms (PAOs) under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Jia et al (2013) reported that in the alternating anaerobic and aerobic bioreactor, the presence of adjacent aerobic and anoxic microzones benefited simultaneous N and P removal due to the activities of denitrifying phosphorus accumulating organisms (DPAOs). However, the composition of the consortium was unclear, and the DPAOs were only enriched in the anoxic phage, its application in real practice was restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al (2013) reported that in the alternating anaerobic and aerobic bioreactor, the presence of adjacent aerobic and anoxic microzones benefited simultaneous N and P removal due to the activities of denitrifying phosphorus accumulating organisms (DPAOs). However, the composition of the consortium was unclear, and the DPAOs were only enriched in the anoxic phage, its application in real practice was restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Both TP and TN removal efficiencies were enhanced along with the decrease of COD/TP ratio, and R3 gained relatively high nitrogen and phosphorus removal efficiency under low COD/TP ratio. It was mainly achieved by some PAOs capable of denitrification, i.e., denitrifying PAOs (DPAOs), using PHA stored in the anaerobic stage as carbon source and nitrite/nitrate as electron acceptors (Jia et al 2013a).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of COD/TP ratio on SND performance (i.e., nutrients removal efficiency) has been reported in our previous work (Jia et al 2013a). As a more fundamental follow-up work, the main effort herein was focused on the microbial community characteristics in order to better understand the underlying mechanisms regarding the impact of COD/TP ratio on SND performance.…”
Section: Responsible Editor: Robert Duranmentioning
confidence: 90%
See 2 more Smart Citations